MOTIVASI BELAJAR ANAK USIA DINI DALAM PROGRAM BELAJAR DARI RUMAH DI MASA PANDEMI COVID-19 - Sri Wahyuni; Azlin Atika Putri; Siti Fadillah (incrementapedia, 2021)
Learning motivation is one of the most important on psychological aspects for students in achieving learning success. The implementation of learning during the corona virus disease 2019 (COVID-19) pandemic in Indonesia using the learning from home “Belajar dari Rumah (BDR)”. This learning program makes children unable to interact directly with their friends and teachers. This fact raises the question, how is children's motivation to learn during the COVID-19 pandemic, at which time children tend to be faced with online learning. This study aims to describe the independence of early childhood who come from poor families. This study uses a quantitative approach with data collection through an e-questionnaire using a google form. The research population is the early age in Pekanbaru City who implement the BDR program. The sample was selected by purposive sampling technique. The instrument used is a psychological scale, namely learning motivation. Overall, from all indicators, children's learning motivation during the COVID-19 pandemic is already in the moderate category, which is 78%. This means that most of the early childhood students who study from home during the COVID-19 pandemic have moderate motivation. 8% of children who are respondents have high motivation to learn and the remaining 14% of children have low motivation to learn.